Effects of polystyrene microplastics on early stages of two marine invertebrates with different feeding strategies. (June 2018) - Messinetti, Silvia; Mercurio, Silvia; Parolini, Marco; Sugni, Michela; Pennati, Roberta
Abstract: Nowadays, microplastics represent one of the main threats to marine ecosystems, being able to affect organisms at different stages of their life cycle and at different levels of the food web. Although the presence of plastic debris has been reported in different habitats and the ability to ingest it has been confirmed for different taxa, few studies have been performed to elucidate the effects on survival and development of marine animals. Thus, we explored the effects of different environmental concentrations of polystyrene microbeads on the early stages of two invertebrate species widespread in the Mediterranean shallow waters: the pelagic planktotrophic pluteus larvae of the sea urchin Paracentrotus lividus and the filter-feeding sessile juveniles of the ascidian Ciona robusta . We evaluated the effects on larvae and juvenile development and determined the efficiency of bead ingestion. The feeding stages of both species proved to be extremely efficient in ingesting microplastics. In the presence of microbeads, the metamorphosis of ascidian juveniles was slowed down and development of plutei altered. These results prompted the necessity to monitor the populations of coastal invertebrates since microplastics affect sensitive stages of life cycle and may have consequences on generation recruitment. Graphical abstract: Image 1 Highlights: Ascidian juveniles and sea urchin plutei are able to ingest microplastics. Animals can expel plastic beads that can be found in the fecal pellet. Survival rate in the short time is not affected by the presence of microplastics. Presence of plastic beads alters metamorphosis of juvenile and body shape of plutei. Filter-feeding animals are more efficient to uptake beads at low concentrations. Abstract : Polystyrene microplastics can alter sensitive developmental stages of marine invertebrates, being filter-feeding organisms more effective in ingesting plastic particles.